Study protocol of a multicentre, randomised, controlled trial evaluating the effectiveness of probiotic and peanut oral immunotherapy (PPOIT) in inducing desensitisation or tolerance in children with peanut allergy compared with oral immunotherapy (OIT) alone and with placebo (the PPOIT-003 study) - Michael O’Sullivan; Michael S Gold; Francesca Orsini; Adriana Chebar Lozinsky; Paxton Loke; Susan L. Prescott; Patrick Quinn; Audrey DunnGalvin; Mimi LK Tang; Anne-Louise Ponsoby; Ee Lyn Su; Marnie Robinson; et al. (BMJ Open)
Introduction Peanut allergy is the the most common cause of life-threatening food-induced anaphylaxis. There is currently no effective long-term treatment. There is a pressing need for definitive treatments that improve the quality of life and prevent fatalities. Allergen oral immunotherapy (OIT) is a promising approach, which is effective at inducing desensitisation; however, OIT has a limited ability to induce sustained unresponsiveness (SU). We have previously shown that a novel treatment comprising a combination of the probiotic Lactobacillus rhamnosus CGMCC 1.3724 with peanut OIT (Probiotic Peanut Oral ImmunoTherapy (PPOIT)) is highly effective at inducing SU, with benefit persisting to 4 years after treatment cessation in the majority of initial treatment responders. Here we describe the protocol for a Phase IIb multicentre, double-blind, randomised, controlled trial (PPOIT-003) with dual primary objectives to evaluate the effectiveness of PPOIT at inducing SU (assessed at 8 weeks after treatment cessation) compared with placebo treatment and peanut OIT alone, in children with peanut allergy.Methods and analysis 200 children 1 to 10 years of age with current peanut allergy confirmed by failed double-blind placebo-controlled food challenge (DBPCFC) at study screening will be recruited from three tertiary paediatric hospitals in Australia. There are three intervention arms—PPOIT, peanut OIT alone or placebo. Interventions are administered once daily for 18 months. The dual primary outcomes are: (1) the proportion of children who attain 8-week SU in the PPOIT group versus placebo group and (2) the proportion of children who attain 8-week SU in the PPOIT group versus OIT group.Ethics and dissemination This study has been approved by the Human Research Ethics Committees at the Royal Children’s Hospital (HREC 35246) and the Child and Adolescent Health Service (RGS 2543). Results will be published in peer-reviewed journals and disseminated via presentations at international conferences.Trial registration number ACTRN12616000322437.